Clinical Characteristics and Efficacy of Adalimumab and Low-Dose Methotrexate Combination Therapy in Patients With Vogt–Koyanagi–Harada Disease - Hiyama, Tomona; Harada, Yosuke; Kiuchi, Yoshiaki (Frontiers in Medicine, 2022)
This retrospective study investigated the clinical characteristics and efficacy of adalimumab and low-dose methotrexate combination therapy in patients with Vogt–Koyanagi–Harada disease who were treated at Hiroshima University from February 2012 to May 2021. The patients’ demographics, clinical features at immunosuppressive therapy administration, steroid-sparing immunosuppressive therapy, side effects, and relapses were recorded. The efficacies of steroid-sparing immunosuppressive therapy (methotrexate, cyclosporine A, adalimumab, and adalimumab and methotrexate combination therapy) were analyzed. Among 62 patients, the median age at diagnosis was 47 years and the median duration of uveitis was 51 months. Systemic corticosteroid therapy was administered in 93.5% of the patients (n=58). In total, 34 patients (54.8 %) were treated with steroid-sparing immunosuppressive therapy. Methotrexate and cyclosporine A were administered in 12 and 22 patients, respectively; relapse occurred in 50.0 % and 22.7 % of the patients, respectively. Discontinuation of cyclosporine was required in 63.6 % of the patients because of side effects. Adalimumab was administered in 14 patients. Recurrence occurred in 11 patients, requiring methotrexate concomitantly. The mean dose of methotrexate at inflammatory quiescence after side effects-related dose decrease was 8.7 mg (0.14 mg/kg). The median duration of combination therapy without recurrence was 20 months. There were no serious adverse events during adalimumab therapy. A high relapse rate was observed in patients receiving MTX; a high rate of side effects requiring discontinuation was observed in patients receiving CsA. Patients with late-stage VKH may achieve better control with adalimumab and methotrexate combination therapy.